Knowledge of ovarian cancer symptoms among women in Palestine: a national cross-sectional study - Mohamedraed Elshami; Areej Yaseen; Mohammed Alser; Ibrahim Al-Slaibi; Hadeel Jabr; Sara Ubaiat; Aya Tuffaha; Salma Khader; Reem Khraishi; Inas Jaber; Zeina Abu Arafeh; Sondos Al-Madhoun; et al. (BMC, 2021)
Abstract Introduction Ovarian cancer (OC) is often diagnosed at advanced stages. This study aimed to assess the Palestinian women's knowledge about OC symptoms and determine the factors associated with having good knowledge. Methods A cross-sectional study was conducted from July 2019 to March 2020 in the two main areas of Palestine: the West Bank and Jerusalem as well as the Gaza Strip. A translated-into-Arabic version of the validated OC awareness measure (OCAM) was utilized for data collection. Stratified convenience sampling was used to recruit adult women attending hospitals, primary healthcare centers, and public spaces at 11 governorates. The knowledge level was categorized into three categories based on the number of symptoms recognized: poor (0 to 4), fair (5 to 8), and good (9 to 11). Results Of 6095 approached, 5618 participants completed the Arabic OCAM (response rate = 92.1%).A total of 5411 questionnaires were included in the analysis: 2278 from the Gaza Strip and 3133 from the West Bank and Jerusalem. Participants living in the West Bank and Jerusalem were older, of higher monthly income, and with more chronic diseases than those living in the Gaza Strip. The most frequently identified symptoms were 'extreme generalized fatigue' (n = 3821, 70.6%), 'unexplained weight loss' (n = 3607, 66.7%), and 'increased abdominal size on most days' (n = 3252, 60.1%). On the other hand, the least recognized symptoms were 'feeling full persistently' (n = 1553, 28.7%) and 'difficulty eating on most days' (n = 1971, 36.4%). Only 943 participants (17.4%) displayed good knowledge of OC symptoms. Participants from the Gaza Strip had a higher likelihood than participants from the West Bank and Jerusalem to have a good level of knowledge (21.0% vs. 14.8%). Being married, knowing someone with cancer, and visiting hospitals were all associated with a higher likelihood of having good knowledge level. However, living in the West Bank and Jerusalem was associated with a lower likelihood of having good knowledge. Conclusion The overall knowledge of OC symptoms in this study was low. Educational interventions are needed to improve Palestinian women's knowledge about OC symptoms.